Nominal Rigidities in a Mail Order Company: Estimation of the Probability of Price Adjustment - Silvia Bertarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
Abstract: Nominal price rigidities are analyzed from two different perspectives. From a qualitative point of view - as Kashyap (1995) - we look for coherent signs which confirm the presence of fixed costs of adjustment, and therefore the validity of state-dependent pricing rules. Our data concern a mail order Italian company and confirm that individual prices do not mimic the aggregate price index, as it was already claimed by Kashyap (1995) and Tsiddon (1993) for US and Israeli data. Second, we estimate by ordered probit models the probability to have nominal price adjustments (increase, rigidity or decrease) as a function of last period real price and rivals' price level. Price point strategies are also investigated. We observe a common performance for all brands' prices which supports a (S, s) rule hypothesis.
Keywords: 330